Silver diamine fluoride: A SMART solution for special care paediatric dentistry - A. Saseendran; P. Urs; N. K. Syeda; F. N. Kandakkeel; A. Selvan; T. Noor; A. K. Tabnjh; S. Selvaraj (Эндодонтия Today, 2025)
AIM. To compare and evaluate the clinical and antimicrobial efficacy of Silver Diamine Fluoride (SDF) and Silver Modified Atraumatic Restorative technique (SMART) in carious primary teeth in children with special needs. MATERIALS AND METHODS. Sixty-six children aged 3–9 years with carious primary molars were randomly divided into two groups. Group I was assigned SDF treatment, and Silver Modified Atraumatic Restorative Treatment (SMART) in Group II. At the baseline and after six months, plaque samples were collected from the buccal and lingual aspect of tooth surface from both the groups using a disposable foam tipped applicators and was transferred into 1 ml of thyoglycolate broth and was incubated at 37°C in Mitis salivarius bacitracin agar plates and Streptocococcus Colony forming units (CFU) were calculated. The participants were recalled after six-month intervals and were evaluated clinically to check the caries adjacent to the restoration by using visual and tactile evaluation and microbiologically to check the status of reduction of CFU in Streptococcus Mutans. SDF was reapplied in Group I and further follow up, re application of SDF in Group I and assessment is being carried out for both the groups. The behavioural assessment of the patient and the acceptance of SDF by the parents as well as the patients were assessed using Likert scale questionnaire. RESULTS. Silver Diamine Fluoride was well accepted by the parents since it provided a minimally invasive treatment approach and caries arrest to the special children. In the present study, SMART’s microbiological and clinical success rate was comparatively higher than SDF. After statistical analysis, with the significant p-value being 0.001 in Group II, it was found that the results obtained were statistically significant and was found that SMART as a better treatment modality. CONCLUSIONS. SMART has gained significant traction due to its effectiveness in arresting the caries. The study promised both clinical and microbiological success rates of SMART when compared with SDF alone.